Synergistic Interaction between Chamomile Flower (Matricaria chamomilla L.) Extracts and Tetracycline Against Wound Infection Bacteria - Ismail, Munira CH; Waleed, Sinai; Ibrahim, Khawla; Fakhri, Noor-Ulhuda (Al-Nahrain Journal of Science, 2018)
In vitro antibacterial activity of Aqueous, ethanol and methanol flower extracts of chamomile alone and in combination with tetracycline by the use of agar well diffusion method against Staphylococcus aureus as gram positive bacterium and Escherichia. coli, Proteus sp. and Klebsiella sp. as gram negative bacteria was studied. It was found that chamomile aqueous extract has no inhibitory effects against gram positive and gram negative bacteria. Ethanolic and methanolic extracts exhibited antibacterial activity against S. aureus at the concentration 1000mg/ml. The diameter of the inhibition zones of S. aureus was 15 mm for Ethanol extract and 12mm at for methanol extract. No antibacterial effect on E. coli, Proteus and Klebsiella for the two extracts. The synergistic effect between the combination of tetracycline with chamomile extracts (ethanol and methanol) (vol./vol.) on S. aureus was studied. It was found that all the combinations proved strong inhibitory effect against S. aureus with different inhibition zone diameters ranged from 23 mm to 35 mm.